Socio-economical contribution and labor allocation of village chicken production of Jamma district, South Wollo, Ethiopia - Mammo, M.; Berhan, T.; Dessie, Tadelle (2008)
The mode of ownership of chicken in the family was various types, for instance shared ownership constituted about (57%) followed by individual ownership (43%) among the members of the households. More than around 70% of overall care-taking of chickens, feeding of chickens, cleaning of birds-quarter, treating of sick birds, decision for off take of poultry products were the responsibility of women. The major criteria used for judging of the price of local chickens were body weight (34.2%), plumage color (33.3%) and comp-type (32.4%). Fluctuations in the prices of the village chicken and chicken-products were mainly due to purchasing power of the consumers (33.4), fasting (33.2), and availability of products (32.5%). Almost all farmers were selling their chicken and chicken products in local markets.